Suitability of Injana Sandstone rocks for building Stone and Rail way ballast stone ̸ Ketol area ̸ Sulymania Governorate - Mohammed R. Abood; Aomed Ahmed Mohammed; Ibrahim Hameed Ibrahim (Tikrit Journal of Pure Science)
The study aims to find the geotechnical properties and engineering geological evaluation of sandston rocks which belong to Injana Formation  ̸ Ketol area ̸ Sulymania  Governorate/formation L belong to Injana  ̸ and make a comparison with Iraqi standard and American society for testing and material (ASTM) specifications. In order to determine their Suitability for building purpose and rail way ballast stone by detailed geological survey of sandstone rocks and laboratory tests (6) station in  addition chemical analysis and mineral components.